Congenital Anomalies Among Newborns in Diyala Province in 2017 - Mahmood Abdulhadi , Samara; Ghazal Noaman, Nadhim; Mansour Hemza, Shefaa (Diyala Journal of Medicine, 2020)
Background: Congenital anomalies or birth defects are groups of disordered of prenatal origin which can be caused by single gene defect, chromosomal disordered, multifactorial inheritance, and environmental teratogens. Objective: To detect the incidence and types of congenital anomalies, as well as other associated factors. Patients and Methods: This study was conducted in Albatool teaching hospital in Baquba city in Diyala government as a cross sectional study of 130 neonates with congenital anomalies from the period of 1st January to 31th December 2017. Patients were categorized according to Age of mother of neonate with congenital anomaly, address, residency, consanguinity between mother and father, mother`s history of Diabetes Mellitus, periconceptional folic acid use, and abortion, also the sex of neonate, gestational age, birth weight, blood group and the type of congenital anomaly. Results: Males were significantly affected (60%) with congenital anomalies than females (37.7%). The percentage of congenital anomalies was more (68.46%) among neonates from consanguineous marriage than neonates from nonconsanguineous marriage (31.54%). Baqubah city was recorded high percentage of anomalies(42.3%), followed by Al-khalis district (24.6%),and then Mukdadia district (15.5%). High percentage of anomalies was recorded among neonates with mothers who did not use folic acid during peri conceptional period (57.7%),and among multiparity (70.76%), premature neonates(57%), caesarean section(60%), low birth weight neonates(53.84%), neonates with blood group O (42.3%), mother`s age 20-35 years (61.54%), and rural residency(69.24%), nervous system anomalies were the most common anomalies(43%), followed by anomalies of circulatory system(21.7%), and then chromosomal abnormalities(7.6%). Conclusion: The most common type of congenital malformations in Diyala government were nervous system malformations. Congenital malformations in Diyala Province were more common in Baquba city and AL Khalis district. Males were significantly affected more than females. Congenital anomalies were significantly more in offspring of consanguineous marriage than of non- consanguineous one. Folic acid usage during peri conceptional period was very important to reduce the incidence of congenital anomalies especially neural tube defects.